The Effect of Giving Bokashi Goat Manure Mixed with Lamtoro on the Growth and Yield of Peanuts (Arachis hypogaea L.) - Ginda Thufriati Sepdelan; Friza Elinda; Dewi Jayagma Ilham; Aulia Meyuliana (Agricultural Revolution Journal, 2025)
Peanuts are a legume commodity that is widely planted in Indonesia, the amount of demand for which continues to increase every year, but it is still not sufficient for the needs in Indonesia. To overcome the problems that occur in the field, organic fertilizer can be used, namely bokashi goat manure mixed with lamtoro, which is expected to reduce the use of inorganic fertilizers. This study aims to determine the effect of providing bokashi goat manure mixed with lamtoro, which is expected to improve soil fertility and the availability of nutrients in the soil. This research was conducted in Jorong Lubuk Pulai, Nagari Sirukam, Payung Sekaki District, Solok Regency. This research was conducted using a Randomized Block Design (RBD) with 6 treatments and 4 groups. The treatments given were goat manure bokashi mixed with lamtoro as much as P0: 0 grams/plant (control), P1: 10 grams/plant, P2: 20 grams/plant, P3: 30 grams/plant, P4: 40 grams/plant, P5: 50 grams/plant. The parameters observed were plant height (cm), number of primary branches (fruit), age at flowering (days), and fresh weight of seeds per plant (g). The provision of bokashi goat manure mixed with lamtoro did not have a significant effect on the observation variables, namely plant height, number of primary branches, flowering age, and fresh seed weight per plant.